2015
DOI: 10.2337/dc14-2472
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Formoterol Diminishes Insulin-Induced Hypoglycemia in Type 1 Diabetes

Abstract: OBJECTIVEHypoglycemia is one of the major factors limiting implementation of tight glycemic control in patients with type 1 diabetes and is associated with increased morbidity and mortality during intensive insulin treatment. β-2 Adrenergic receptor (AR) agonists have been reported to diminish nocturnal hypoglycemia; however, whether long-acting inhaled β-2 AR agonists could potentially be used to treat or prevent hypoglycemia has not been established.RESEARCH DESIGN AND METHODSSeven patients with type 1 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…While muscle hypertrophy is scarcely explored for the inhaled route, daily inhalation of terbutaline at 4 mg (8 puffs from a 0.5 mg Turbohaler) for 4 weeks was recently shown to induce a 1 kg gain in lean mass in healthy young men . In addition, an inhaled dose of 54 μg formoterol (6 puffs from a 9 μg Turbohaler), a dose that lies within the current WADA threshold limit, induces skeletal muscle signalling and increases resting metabolic rate, fat oxidation, and peripheral glucose uptake . The same is the case for salbutamol, which via the inhaled route has been shown to induce lipolysis at therapeutic doses and to increase resting metabolic rate .…”
Section: Inhalation Of Beta2‐agonists At High Doses Exerts Similar Efmentioning
confidence: 99%
See 1 more Smart Citation
“…While muscle hypertrophy is scarcely explored for the inhaled route, daily inhalation of terbutaline at 4 mg (8 puffs from a 0.5 mg Turbohaler) for 4 weeks was recently shown to induce a 1 kg gain in lean mass in healthy young men . In addition, an inhaled dose of 54 μg formoterol (6 puffs from a 9 μg Turbohaler), a dose that lies within the current WADA threshold limit, induces skeletal muscle signalling and increases resting metabolic rate, fat oxidation, and peripheral glucose uptake . The same is the case for salbutamol, which via the inhaled route has been shown to induce lipolysis at therapeutic doses and to increase resting metabolic rate .…”
Section: Inhalation Of Beta2‐agonists At High Doses Exerts Similar Efmentioning
confidence: 99%
“…Because of their ability to increase metabolic rate, beta 2 ‐agonists are considered to be thermogenic substances and their effects on fat oxidation are well documented . Aside from inducing lipolysis in adipose tissue and pancreatic insulin production and release, beta 2 ‐agonists have a range of other systemic effects, including stimulation of hepatic glucose production and release, and epinephrine release, among other effects . Thus, the mechanisms underlying the changes in metabolism induced by beta 2 ‐agonists are complex and possibly involve several tissues.…”
Section: Mechanisms Underlying the Lipolytic And Metabolic Actions Ofmentioning
confidence: 99%
“…More recently, there has been significant interest in discovering how cytokine, purine, steroid, opiate, β 2 -adrenergic or serotonergic signalling may play roles in the development of IAH [22,[38][39][40][41][42]. These extracellular signals are able to modulate firing rates of glucose-sensing neurons.…”
Section: Why Do People With Diabetes Develop Iah?mentioning
confidence: 99%
“…This knowledge has been derived from laboratory-based research, which has enabled proof-of-concept clinical trials. For instance, the inhaled highly-selective β 2 -adrenoreceptor agonist formoterol fumerate was shown to amplify the CRR to hypoglycaemia in a small group of participants with type 1 diabetes [42], while oral dehydroepiandrostenedione (DHEA), which has both anti-corticosteroid and anti-GABA activity, blunted the suppressive effect of recurrent hypoglycaemia on subsequent hypoglycaemia CRR in individuals without diabetes [39]. It is interesting that many of these extracellular signals help coordinate the body's response to a wide variety of physiological stressors and play roles in both amplifying the acute response to a given stressor and initiating subsequent adaptive responses that are designed to protect cells during subsequent exposure to that stressor.…”
Section: Why Do People With Diabetes Develop Iah?mentioning
confidence: 99%
“…[7][8][9] However, pharmacological treatments with beta2-agonists and opioid antagonists have also been tested for prevention and treatment of hypoglycaemia. [10][11][12][13] Nakao et al 14 reported that plasma beta-endorphins are released in response to insulin-induced hypoglycaemia. Subsequent studies found that an intravenous infusion of naloxone, an opiate receptor blocker, enhanced the counter-regulatory hormone response to hypoglycaemia in dogs, 15 as well as in healthy non-diabetic humans and in patients with T1DM.…”
Section: Introductionmentioning
confidence: 99%